Penerapan Sistem Informasi Geografis untuk Optimalisasi Lahan Pertanian Berkelanjutan di Kabupaten Kupang - Vito Daniel Boboy; Yampi R Kaesmetan (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
Kupang Regency in East Nusa Tenggara Province has great potential in the agricultural sector, but faces various challenges that can hinder sustainable productivity, such as declining soil quality, land degradation, and changes in rainfall patterns due to the impact of climate change. Therefore, sustainable agricultural land management is very important in maintaining regional food security and increasing agricultural production. This study aims to develop a web-based Geographic Information System (WebGis) that is capable of mapping agricultural land conditions in Kupang Regency. This system is designed to present spatial information on soil fertility levels, the existence of critical land, and the impact of climate variability on agricultural areas. In the process of land analysis and classification, the Self-Organizing Map(SOM) method is used, an unsupervised learning approach that is effective in grouping data based on certain characteristics. The mapping results are then integrated into the WebGis platform so that they can be accessed interactively and easily used by the Department of Agriculture or related policy makers. With this system, it is expected to assist in making more precise, efficient, and sustainable data-based decisions, especially in agricultural land planning and management. Overall, this research is expected to provide a real contribution in efforts to increase the efficiency of land use and encourage environmentally friendly agricultural practices in Kupang Regency.